Community ecology of the metazoan parasites of Atlantic Moonfish, Selene setapinnis (Osteichthyes: Carangidae) from the coastal zone of the state of Rio de Janeiro, Brazil - Cordeiro,A. S. (2004)
Eighty-nine specimens of Selene setapinnis (Mitchill, 1815) collected from the coastal zone of the State of Rio de Janeiro (21-23ºS, 41-45ºW and 23º05'S, 44º30'W), Brazil, from August 2001 to May 2002, were necropsied to study their metazoan parasites. Eighty-one (91%) specimens of S. setapinnis were parasitized by one or more metazoan species. Twenty-one species of parasites were collected: 8 digeneans, 3 monogeneans, 2 cestodes, 5 nematodes, and 3 copepods. The endoparasites (digeneans, cestodes, and nematodes) were 74.1% of total number of parasite specimens collected. The monogenean Pseudomazocraes selene (Hargis, 1957) was the most dominant species with the highest prevalence in the parasite community of S. setapinnis. The metazoan parasites of this host species showed the typical aggregated pattern of distribution. Only one parasite species (Acanthocolpoides pauloi Travassos, Freitas & Buhrnheim, 1955) showed positive correlation between the host total length and parasite abundance in S. setapinnis. Caligus robustus Bassett-Smith, 1898, P. selene, and Terranova sp. demonstrated positive correlation between the host total length and prevalence. Larvae of Terranova sp. showed influence of the host sex on its prevalence. A pair of ectoparasite species, P. selene-C. robustus, exhibited positive covariation between their abundances. Two pairs of endoparasite species, L. microstomum-P. merus and A. pauloi-P. merus showed significant covariation among their abundances; and the pair Terranova sp.-Raphidascaris sp. had positive co-ocorrence and covariation in the infracommunities of S. setapinnis. Like the parasite communities of the other carangid fishes from Rio de Janeiro, the parasite community of S. setapinnis is apparently only a slightly ordered species complex, characterized by dominance of endoparasite species.